How to Stop School Rampage Killing: Lessons from Averted Mass Shootings and Bombings - Madfis, Eric (Springer eBook Collection, 2020)
1. Introduction -- 2. Assessing School Rampage -- 3. Confidence and Doubts about Assessing Rampage -- 4. Preventing School Rampage -- 5. Conclusion -- 6. Methodological Appendix.